Tahapan Kegiatan dan Kendala Pelaksanaan Program UPPO pada Subak Abian Suka Maju di Desa Landih, Kecamatan Bangli, Kabupaten Bangli - MULIAWAN, I WAYAN EKA; ASTITI, NI WAYAN SRI; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.4, Oktober 2019, 2019)
Procedures and Obstacles in The Implementation of Organic Fertilizer Production Unit in SubakAbianSukaMaju at Landih Village, Bangli District, Bangli Regency The Organic Fertilizer Production Unit (UPPO) is one of the government’s efforts to support the supply availability of organic fertilizer for farmers. The purpose of the research is to know the procedures and obstacles of UPPO program implementation in SubakAbian (Traditional Agrarian Organization) SukaMaju at Landih Village, Bangli District, Bangli Regency. The data was collected through interview and documentation. 48 respondents were determined through purposive sampling method. The instrument of the research used questionnaires and interview guidelines. The analysis method was descriptive qualitative analysis. The procedure of UPPO at SubakAbianSukaMaju began from the preparation stage which consists of socialization, agreement making, and organization forming. After the preparation stage, comes the execution stage which consists of location determination, infrastructure construction, cage construction, livestock purchasing, and facilities preparation. The last stage is the production, such as the livestock sales benefit and manure. The execution stage is categorized as good because the facilities well-supported the activity. The obstacles of the program implementation are such as technical issues in preparing the infrastructures and facilities, economic issues in allocating the aid fund as well as the return of cow sales benefit. There are also several social issues such as the low education of the members, weak aspiration of the members, no leader figure within the society, and the lack of innovation.It is recommended for the government to better monitor the UPPO program implementation, to mentor and assist the farmers, and to complete the infrastructure and facilities that the UPPO lack of, such as the fermentation tub, three-wheel vehicles, organic fertilizer manufacturing machines, animals’ health certificate, and medicines for the livestock.